The impact of Covid-19 on areas prone to traffic accidents in Depok City : Margonda Raya Road case study - Muhammad Isradi (Journal of World Conference (JWC), 2021)
Traffic accidents and congestion is one of the main problems in Depok city. Jalan Margonda Raya is one of the streets in Depok city. Jalan Margonda Raya is one of the roads in Depok city with quite high traffic activity. To prove this, research is done by analyzing the area of accident prone and road performance with the aim of analyzing the areas prone to traffic accident and know the performance of mesh and how to correct alternative solution to overcome it. The method used in this research to analyse areas prone to accident is to use the AEK (equivalent number of accident) approach, and to know the area of traffic accident (black spot) with the method BKA (upper control limit), while to know the performance of the segment using Manual Road capacity 1997. Based on the results of analysis concluded that Jalan Margonda Raya, belongs to the category of road prone traffic accidents, because it has a value of AEK greater or greater than the value of BKA and UCL. Road with the highest AEK value is Jalan Margonda Raya with a value of AEK 40 where the value of BKA is only 24.250 and UCL value of 35.949. On the road, there have been 4 accidents with the total death toll of 1 person, 3 people with severe injuries, a light injury of 5 people, and a material loss of 5.3 million Rupiah. The most common type of accident is the front-back sprinrack of 45.45% of the total number of accidents. The most common time for accident at Jalan Margonda Raya Depok is at night at 18.00 WIB – 06.00 WIB with a percentage of 63.63% from the total accident. As for the level of service on Jalan Margonda Raya Sunday Direction Jakarta-Depok is B, this is due to the degree of saturation (V/C ratio) of 0.530, while the direction of Depok-Jakarta is B, this is because the degree of saturation (V/C ratio) of 0.540 and for the day, Monday 15 May 2020 direction Jakarta-Depok is B, this is because the degree of saturation (V/C ratio) of 0.669 while the direction of Depok-Jakarta is B, this is because the degree of saturation (V/C 0.608 From the analysis obtained some alternative solution that is to install and repaint road markers and Zebra Cross, repaint on sidewalks or kerb, and do periodic supervision work, check periodically on street lighting lamps.